Influence of thermal expansion on shrinkage during photopolymerization of dental resins based on bis-GMA/TEGDMA - Mucci, Veronica Lujan (2009)
Objective: The aim of this study was to assess volume changes that occur during photopolymerization of unfilled dental resins based on bis-GMA-TEGDMA. Methods: The resins were activated for visible light polymerization by the addition of camphorquinone (CQ) in combination with dimethylamino ethylmethacrylate (DMAEMA) or ethyl-4-dimethyl aminobenzoate (EDMAB). A fibre-optic sensing method based on a Fizeau-type interferometric scheme was employed for monitoring contraction during photopolymerization. Measurements were carried out on 10 mm diameter specimens of different thicknesses (1 and 2 mm). Results: The high exothermic nature of the polymerization resulted in volume expansion during the heating, and this effect was more pronounced when the sample thickness increased. Two approaches to assess volume changes due to thermal effects are presented. Due to the difference in thermal expansion coefficients between the rubbery and glassy resins, the increase of volume due to thermal expansion was greater than the decrease in volume due to thermal contraction. As a result, the volume of the vitrified resins was greater than that calculated from polymerization contraction. The observed trends of shrinkage versus sample thickness are explained in terms of light attenuation across the path length during photopolymerization. Significance: Results obtained in this research highlight the inherent interlinking of non-isothermal photopolymerization and volumetric changes in bulk polymerizing systems. © 2008 Academy of Dental Materials.